2022
DOI: 10.3389/fmicb.2022.957148
|View full text |Cite
|
Sign up to set email alerts
|

Microbial detoxification of mycotoxins in food

Abstract: Mycotoxins are toxic secondary metabolites produced by certain genera of fungi including but not limited to Fusarium, Aspergillus, and Penicillium. Their persistence in agricultural commodities poses a significant food safety issue owing to their carcinogenic, teratogenic, and immunosuppressive effects. Due to their inherent stability, mycotoxin levels in contaminated food often exceed the prescribed regulatory thresholds posing a risk to both humans and livestock. Although physical and chemical methods have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 139 publications
0
7
0
Order By: Relevance
“…Both A. flavus and A. parasiticus produce AFB 1 and AFB 2 , whereas AFG 1 and AFG 2 are produced solely by A. parasiticus (Muaz et al., 2022). Animal liver cytochrome P450 enzymes convert AFB 1 and AFB 2 into their respective C 4 hydroxylated metabolites, AFM 1 and AFM 2 , from where these become part of their milk (Abraham et al., 2022; Ismail et al., 2016). The different forms of AFs can undergo inter‐conversion as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Both A. flavus and A. parasiticus produce AFB 1 and AFB 2 , whereas AFG 1 and AFG 2 are produced solely by A. parasiticus (Muaz et al., 2022). Animal liver cytochrome P450 enzymes convert AFB 1 and AFB 2 into their respective C 4 hydroxylated metabolites, AFM 1 and AFM 2 , from where these become part of their milk (Abraham et al., 2022; Ismail et al., 2016). The different forms of AFs can undergo inter‐conversion as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional detoxification methods for mycotoxins involve physical, chemical, and microbial approaches. , However, these methods possess drawbacks such as nutrient loss, reagent residues, and secondary pollution to the environment. , In contrast, enzymatic degradation offers advantages, including mild reaction conditions, high efficiency, low cost, and convenient operations. , Fungal laccases (EC 1.10.32) have attracted considerable attention due to their environmentally friendly characteristics and catalytic properties, such as high oxidation–reduction potentials, wide temperature ranges, and maximum activity under acidic conditions. , These characteristics make them suitable for use in food and feed environments . To date, several studies have reported the efficiency of laccases from fungi and bacteria in degrading AFB 1 and ZEN.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional detoxification methods for mycotoxins involve physical, chemical, and microbial approaches. 11, 12 However, these methods possess drawbacks such as nutrient loss, reagent residues, and secondary pollution to the environment. 13,14 In contrast, enzymatic degradation offers advantages, including mild reaction conditions, high efficiency, low cost, and convenient operations.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Despite the diversity of methods used to try to reduce pollution from mycotoxins in different agricultural crops and animal feeds, including chemical, physical, and biological methods, they have not been ideal in all tests. Physical methods, which involve adding various adsorbents such as clay minerals, organic and biological compounds, are the most commonly used methods because they are safer than other methods and are simple to use, in addition to their encouraging or satisfactory results [5]. Microorganisms represented by different types of bacteria and yeasts, has been used in many studies to investigate the ability of these microorganisms to adsorb various toxins from liquid media such as milk or contaminated juices [6,7].…”
Section: Introductionmentioning
confidence: 99%